1996
DOI: 10.3109/03005369609076782
|View full text |Cite
|
Sign up to set email alerts
|

Women with noise-induced hearing loss: An invisible group?

Abstract: The aim of this qualitative study was to describe, from the perspective of women with noise-induced hearing loss (NIHL), their experiences of noise as a threat to health and their having to live with a hearing disability, i.e. behaviours, thoughts and emotions in auditory demanding situations. Ten women, patients with NIHL at the Department of Audiology, Borás' Hospital in Sweden, were selected to form a heterogeneous sample. A taped in-depth interview, lasting from 45 minutes to 1 hour, was conducted with eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…Stereotypes about hearing loss can strain social exchanges and often lead to avoidance tendencies (Hallberg & Barrenas, 1995;Hallberg & Jansson, 1996). H é tu (1996) described how people with an acquired hearing loss often concealed hearing diffi culties and were reluctant to acknowledge hearing loss in some social settings.…”
Section: Sumariomentioning
confidence: 98%
See 1 more Smart Citation
“…Stereotypes about hearing loss can strain social exchanges and often lead to avoidance tendencies (Hallberg & Barrenas, 1995;Hallberg & Jansson, 1996). H é tu (1996) described how people with an acquired hearing loss often concealed hearing diffi culties and were reluctant to acknowledge hearing loss in some social settings.…”
Section: Sumariomentioning
confidence: 98%
“…It is therefore diffi cult for some people with hearing impairment to identify decline in their hearing ability, and this might serve to delay help-seeking (Garstecki, 1990;Gilhome et al, 1990). Acceptance of hearing loss into one ' s self/social identity is likely an important antecedent to an individual seeking help (Goffman, 1963;Hallberg & Jansson, 1996;H é tu, 1996). Hallberg and Jansson (1996) reported that (over time) some people move in and out of denial and acceptance of hearing loss.…”
Section: Sumariomentioning
confidence: 98%
“…Only one study addressed the perspective of employees with rheumatoid arthritis, the challenges they face at work, and the adaptations they need (10). With respect to hearing loss, some studies focused on social interactions at work, (11) while others only dealt with noise-induced hearing loss (12)(13)(14)(15) or registered the effects of early intervention from the doctor's perspective (16). Although there are many studies on work-related problems associated with diabetes mellitus, they do not relate to the patient's experience of working with a chronic illness, but focus on functional and mental abilities (17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…They also found that more advanced HI was associated with frequent use of both non-verbal and verbal strategies, whereas we found that only verbal strategies were positively associated with advanced HI. Communication strategies have previously been studied in relation to the stigma attached to HI (Garstecki & Erler 1999), the ''communication climate'' (Hallberg & Jansson 1996), and one's own acceptance of HI (Hallberg, Johnson & Axelsson 1993). Even if such relations were beyond the scope of the present paper, they may explain why we found that degree of HI had low or no impact on use of verbal and nonverbal coping strategies, respectively.…”
Section: Coping Strategiesmentioning
confidence: 50%